Non-invasive molecular barcode assay for diagnosis of sex hormones correlated with precocious puberty - Lee, Hyojin; Kim, Ki Hun; Lee, Kwan Hyi (ELSEVIER SCIENCE SA, 2019)
Precocious puberty treatment in children faces several diagnostic and therapeutic challenges. For an efficient prognosis of the disease, early diagnosis must be accompanied by properly timed treatment. Sex hormones are markers that are used to diagnose precocious puberty. Detection methods usually require multiple blood samples from the patient over a 90-120-min time interval. The WA is painful and uncomfortable for children, and is relatively expensive and time-consuming. Herein, we introduce a new bio-barcode method that is a non-invasive, fast, highly-sensitive, and is capable of multiplex detection of steroid sex hormones in urine using gold nanoparticles. We compared three different barcode assay approaches to determine the barcode molecules: gel electrophoresis, fluorescence-based solution assay, and liquid chromatography-mass spectrometry (LC-MS). The gel electrophoresis approach was cost-effective but could not quantify the absolute levels of hormones. The other methods permitted quantitative comparison between samples. LC-MS displayed the highest sensitivity. For the LC-MS analysis, we grafted two chemical compounds as surrogate molecules onto the surface of 50-nm gold nanoparticles. Approximately 7-9 million chemical molecules were loaded on each nanoparticle, which amplified the LC-MS signal. The LC-MS could detect hormones levels which were 10,000-fold lower than the levels detected by the conventional method. The barcode assay could determine multiple analyzes simultaneously without any sample preparation step. Importantly, this is first finding that uses barcode molecules-conjugated nanoparticles to amplify the mass spectrometer signal. The result is significant as it has implications for its principle and methodology, which utilizes non-invasive procurement protocols, can be applied to not only sex hormones, but other hormones which require will ultrasensitive detection. We anticipate that our research findings, which use a painless and economic detection method, can contribute to the early and accurate diagnosis of precocious puberty.
Keywords: MASS-SPECTROMETRY; ULTRASENSITIVE DETECTION; FUSION GENES; 17-BETA-ESTRADIOL; PROTEIN; ESTRADIOL